2012
DOI: 10.1111/j.1601-183x.2012.00830.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection for high alcohol preference drinking in mice results in heightened sensitivity and rapid development of acute functional tolerance to alcohol's ataxic effects

Abstract: Propensity to develop acute functional (or within session) tolerance to alcohol (ethanol) may influence the amount of alcohol consumed, with higher drinking associated with greater acute functional tolerance (AFT). The goal of the current study was to assess this potential correlated response between alcohol preference and AFT in second and third replicate lines of mice selectively bred for high (HAP2&3) and low (LAP2&3) alcohol preference drinking. Male and female mice were tested for development of AFT on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 37 publications
3
38
1
Order By: Relevance
“…Similar to the human literature, studies have shown that these opposite genetic predispositions can associate with highly different responses to alcohol in these lines of rodents (Chester, Lumeng, Li, & Grahame, 2003; Crabbe, Colville, et al, 2012; Crabbe, Kruse, et al, 2012; Fritz et al, 2014; Fritz, Grahame, & Boehm, 2013; Grahame, Rodd-Henricks, Li, & Lumeng, 2000; Waller, McBride, Lumeng, & Li, 1983), suggesting that these responses ‘genetically correlate’ with the alcohol consumption phenotype. In other words, these associations can be indicative of common underlying genes for the response(s) of interest and form of alcohol consumption.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…Similar to the human literature, studies have shown that these opposite genetic predispositions can associate with highly different responses to alcohol in these lines of rodents (Chester, Lumeng, Li, & Grahame, 2003; Crabbe, Colville, et al, 2012; Crabbe, Kruse, et al, 2012; Fritz et al, 2014; Fritz, Grahame, & Boehm, 2013; Grahame, Rodd-Henricks, Li, & Lumeng, 2000; Waller, McBride, Lumeng, & Li, 1983), suggesting that these responses ‘genetically correlate’ with the alcohol consumption phenotype. In other words, these associations can be indicative of common underlying genes for the response(s) of interest and form of alcohol consumption.…”
Section: Introductionsupporting
confidence: 68%
“…Three replicates of the HAP/LAP lines now exist and there are extreme differences in alcohol intake and preference with the replicate HAP lines consuming high, intoxicating amounts of alcohol, and replicate LAP lines demonstrating relative avoidance (Oberlin et al, 2011). Only HAP2 mice were used as we previously demonstrated that the genetic differences in ataxic ethanol sensitivity and AFT were present in both replicates 2 and 3 (Fritz et al, 2013). Therefore, testing replicate 3 was deemed unnecessary.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, identifying a simple relationship between tolerance and drinking in model systems has been difficult. The relationship between tolerance and drinking appears to depend on how tolerance was induced and how it was measured (Crabbe et al, 2012;Fritz, Grahame, & Boehm, 2013). Acute tolerance has been described in worms and mammals, but not in flies.…”
Section: Tolerancementioning
confidence: 96%